Disgesting the tropic : the aura ofIndo-Mauritian spirituality implicit intheaestheticisation of coconut water’ssocial life - Kantu, Asso'o Jeanne Rita (My University, 2017)
BasedonanethnographicstudyoftwoIndo-MauritianfamiliesineasternMauritius,their gatheringsandtheirritualsbasedonanHindufaith,thisresearchreportstudiestherelationship betweenaesthetics,spiritualityandaurainthemasscommoditizationandadvertisingofbottled coconutwater.Usingparticipantobservation,in-depthinterviewsandsemioticimageryanalysis, thisreportsuggeststhatthecoconut,inHindubelief,hasavitalmaterialityandcariesanaurain itsphysicalcompositionandphysiologicalcontentwhich:1)allows it to travel across pace and time2)endowsitwitha‘divinity’thatvalidatesitseconomicexploitandrepresentationand3) standsasanOrientalistmacrocosmicsymbolforthemicrorealities,intimacies,socialrelations and lived experiences of every day life on a ‘paradise’ island. Keywords:aura ,aesthetic, spiritualty, Hindu, Indo-Mauritian, vitalmateriality
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts(Coursework and Research Report) in Social Anthropology By ASSO’OJEANNERITAKANTU Supervisor: Associate Professor SharadChari (CISA) UniversityoftheWitwatersrand &Centre for IndianStudies in Africa (CISA) August 2017
Keywords: Religions; Ethnology--Religious aspects